2014
DOI: 10.1007/s13312-014-0543-4
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines on management of childhood convulsive status epilepticus

Abstract: Each institution should use a pre-determined protocol for management of status epilepticus; pre-hospital management and early stabilization is the key to a satisfactory outcome of status epilepticus. Pharmacotherapy should not be delayed for any investigations; the initial management should consist of a parenteral benzodiazepine by any route feasible. Subsequent management has been detailed. The group also felt the need for more epidemiological research on status epilepticus from India, and identified certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 99 publications
2
43
0
Order By: Relevance
“…In a comparative study in children, it was reported as effective as valproate and safer in the control of refractory SE 13 . Review of literature shows that use of LEV is considered safe and effective in children with refractory SE [13][14][15] . In a report of two years' experience with this drug in SE, no severe adverse reactions were observed 16 .…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study in children, it was reported as effective as valproate and safer in the control of refractory SE 13 . Review of literature shows that use of LEV is considered safe and effective in children with refractory SE [13][14][15] . In a report of two years' experience with this drug in SE, no severe adverse reactions were observed 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though generalized convulsive status epilepticus in adults and older children >5years refers to more than 5 min of continuous seizures or two or more discrete seizures between which there is incomplete recovery of consciousness, in view of most previous studies on status epilepticus having been done using the 30 minute definition, this study also has been done using 30 minutes definition. 3 Prolonged or refractory status epileptius is defined as seizures that persist despite the administration of two appropriate anticonvulsants at acceptable doses, with a minimum duration of status of 60 minutes (by history or in observation). 3 Shock and indication for intubation are defined according to PALS Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…3 Prolonged or refractory status epileptius is defined as seizures that persist despite the administration of two appropriate anticonvulsants at acceptable doses, with a minimum duration of status of 60 minutes (by history or in observation). 3 Shock and indication for intubation are defined according to PALS Guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…3 The use of operational definition allows early treatment before the seizure becomes refractory to antiepileptic drugs. 4 Prolonged status epilepticus can lead to various complications such as cardiac dysrhythmia, metabolic derangements, autonomic dysfunction, neurogenic pulmonary oedema, hyperthermia, pulmonary aspiration and even permanent neurological damage. Approximately 4-10% of children experience one episode of seizure within first 16 years of life.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, the 'Multi-disciplinary Group on Management of Status Epilepticus in Children in India' in a consensus guideline has highlighted the need for research on epidemiology and outcome of SE in Indian children. 4 This study was undertaken as an attempt to describe clinical profile and outcome of children with convulsive status epilepticus presenting to pediatric intensive care unit (PICU) in a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%